The normative gap in the confidentiality of deeds by instrumentary witnesses and its legal consequences for notary liability under Indonesian law - Livia Angie Tania; Sausan Qanita Alfaj (Journal of Law Science, 2026)
This study aims to analyze the normative gap regarding the obligation of confidentiality of instrumentary witnesses in the drafting of authentic deeds and its implications for notarial liability within the framework of positive law in Indonesia. The novelty of this study lies in its focus on the unregulated legal position of instrumentary witnesses in relation to deed confidentiality, an issue that has received limited attention in previous notarial legal studies which generally emphasize notary obligations only. The study also offers an explicit scientific contribution by constructing the legal relationship between witness confidentiality obligations and notary liability through the integration of civil, criminal, and personal data protection perspectives. The method employed is normative legal research using statutory and conceptual approaches through analysis of Article 16 paragraph (1) letter e, Article 38, and Article 40 of Law Number 30 of 2004 concerning Notary Office as amended by Law Number 2 of 2014, Article 1868 of the Indonesian Civil Code, Articles 1365 and 1367 of the Indonesian Civil Code, Article 322 of the Criminal Code, and Law Number 27 of 2022 concerning Personal Data Protection. The results identify three principal findings. First, there is a normative gap because instrumentary witnesses have direct access to deed contents but are not expressly bound by statutory confidentiality obligations, creating legal uncertainty in notarial practice. Second, despite the absence of explicit regulation, instrumentary witnesses may still incur civil liability under Article 1365 of the Civil Code and potential criminal liability under Article 322 of the Criminal Code when disclosure causes legal harm. Third, notaries may remain responsible under the principle of prudence and supervisory liability under Article 1367 of the Civil Code, resulting in disproportionate allocation of legal responsibility. Theoretically, this study strengthens the doctrine of confidentiality in authentic deed formation by extending responsibility beyond the notary alone. Practically, it supports the need for reformulation of notarial norms to establish explicit confidentiality obligations for instrumentary witnesses and ensure proportional legal protection for all parties.